2019
DOI: 10.1093/braincomms/fcz019
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic assays in yeast and zebrafish reveal drugs that rescue ATP13A2 deficiency

Abstract: Mutations in ATP13A2 (PARK9) are causally linked to the rare neurodegenerative disorders Kufor-Rakeb syndrome, hereditary spastic paraplegia and neuronal ceroid lipofuscinosis. This suggests that ATP13A2, a lysosomal cation-transporting ATPase, plays a crucial role in neuronal cells. The heterogeneity of the clinical spectrum of ATP13A2-associated disorders is not yet well understood and currently, these diseases remain without effective treatment. Interestingly, ATP13A2 is widely conserved among eukaryotes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…As SDS is inherently toxic, compounds reducing its toxic properties could also be identified and, thus, the other phenotype—cadmium sensitivity—was subsequently tested (see below). We screened the Prestwick drug repurposing library (Prestwick Chemical) previously used in such screens [ 48 , 50 ], which contains drugs accepted for use in humans. Active compounds were identified after 3–5 days by the observation of growth zones around the filter.…”
Section: Resultsmentioning
confidence: 99%
“…As SDS is inherently toxic, compounds reducing its toxic properties could also be identified and, thus, the other phenotype—cadmium sensitivity—was subsequently tested (see below). We screened the Prestwick drug repurposing library (Prestwick Chemical) previously used in such screens [ 48 , 50 ], which contains drugs accepted for use in humans. Active compounds were identified after 3–5 days by the observation of growth zones around the filter.…”
Section: Resultsmentioning
confidence: 99%
“…Further consolidating our results, we found that GPDs accumulate in a similar manner in MUT2 larvae compared with WT2 larvae, demonstrating that CLN3 function is also invalidated in this line. Interestingly, using our targeted LC-MS/MS method, we did not find accumulation of GPDs in a zebrafish model knocked out for ATP13A2/CLN12 (previously described in reference 35 ), suggesting that the abnormal GPD levels might be specific to CLN3 loss of function and not generalizable to all other NCL genes ( Fig S9B ). We also measured GPDs in human-induced pluripotent stem cell–derived cerebral organoids, a state-of-the-art human model for brain development previously described in references 18 and 36 .…”
Section: Resultsmentioning
confidence: 49%
“…9A). Interestingly, using our targeted LC-MS/MS method, we did not find accumulation of GPDs in a zebrafish model knocked out for ATP13A2/CLN12 (previously described in (Heins-Marroquin et al 2019)), suggesting that the abnormal GPD levels might be specific for CLN3 lossof-function and not generalizable to all other NCL genes (Supplementary Fig. 9B).…”
Section: Validation Of Metabolic Disruptions and Assessment Of Lysoso...mentioning
confidence: 55%
“…during early developmental stages, suggests that GPD metabolism is very tightly connected to CLN3 function. The absence of GPD accumulation in our zebrafish model for ATP13A2/CLN12 deficiency (Heins-Marroquin et al 2019), also leading to neuronal lipofuscinosis (Farias et al 2011; Bras et al 2012; Matsui et al 2013), indicates that these compounds may be specific for certain types of NCLs, a hypothesis that will now need to be tested in different models and non-CLN3 Batten disease patients. The zebrafish model has the potential to fill the gaps between cell culture and mammalian models and accelerate the understanding of early metabolic events that lead to the development of a childhood disease that, as of today, is still invariably lethal.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation